Adaptive Voltage Control for DC Motors of Omnidirectional Mobile Robot With Prevent Wheel Slippage - Hoa Thi Truong (IEEE Access)
Omnidirectional mobile robots (OMRs) are widely recognized in the industry for their excellent maneuverability and flexibility, particularly when navigating complex environments. Standard designs typically feature three wheels powered by direct current (DC) motors. However, precise control of these systems remains challenging due to the nonlinear traction dynamics between the wheels and the ground, leading to slipping and instability, mainly when operating in changing surface conditions or sudden movements. Traditional control methods often fail to comprehensively address these issues, especially in ensuring accurate path tracking and dynamic adaptation to changes in traction force without encountering controller singularities or input constraints. This study proposes an adaptive voltage controller for three-wheeled omnidirectional robots driven by DC motors to address these challenges. The controller’s contribution is its ability to dynamically limit the input voltage based on real-time wheel and ground traction force estimates, thus effectively preventing wheel slippage. The controller consists of three main components: 1) an adaptive tracking controller that ensures the system states converge rapidly to the desired trajectory, 2) a transient singularity-free controller that resolves the singularities associated with traditional adaptive control laws, and 3) a backend system designed to adapt to input voltage constraints. The proposed controller has been applied to the path tracking of an omnidirectional mobile robot and has demonstrated outstanding performance through numerical simulations. When implemented in various environments, the proposed controller shows significant advantages over conventional controllers.